Avaliação da alteração de placas de rocha em fachada: estudo de caso - Coêlho, Lavínia de Vasconcelos Xavier (2006)
A facade coating is, by itself, a system of complex solution. It envelops a series of variables such as project conception, material specification, execution and maintenance. And, even with all aspects well attended, one can not determine the system useful life, because the environment has a strong influence in its durability. The use of dimension stones as coating element is another item that needs attention, since rocks have an uncontrollable composition, are anisotropic regarding resistance, are normally unstable before inclemency of the weather and being tile its thickness has been reduced, weakening them and diminishing protection to the building body. This work is about a case study where granite tiles (200x400xl0 mm), commercially named "cinza andorinha" have been used, fixed by chemical anchorage, held by clamps, in a region with high humidity, high isolation, subjected to sea mist and pollution, Recife (PE) metropolitan region. Through the method proposed by Lichtenstein (1986) it was made a facade inspection and several pathologies were found, such as tiles fall, infiltration and clamps oxidations and the granite tiles preseting chemical physical and biological alteration such as change in color, salt crystallization, efflorescence, mineral oxidation, disagregation, cracking, and microorganism aggression. As a result, the following cosiderations were done about the facade; constructive method, emphasizing the project importance (specially the constructive detail): material specification in compatibity with the situation subdued; execution and maintenance. Likewise, the granite alteration was analyzed. Features as change in composition (biotite oxidation) and in microstructure (salt crystallization) were studied aiming to contribute for a more rational use of this specific building material